ANALISA KONDISI KERUSAKAN LAPISAN PERMUKAAN JALAN DESA SAKA – WAILULU SERAM UTARA BARAT KABUPATEN MALUKU TENGAH - Purwanto, Hadi; Soumokil, Musper David; Sihasale, Stephanie Jenifer (Jurusan Teknik Sipil, 2024)
Highways are one of the supporting facilities for an area that can accelerate economic growth and development in that area. The highway in Saka - Wailulu Village is located on Jalan Taniwel - Saleman, one of the national roads in Maluku Province, Central Maluku Regency, North West Seram District. This research aims to determine the condition and type of road damage and determine the PCI value. The PCI method is a method that can assess the type of road pavement damage and the severity of the road. The results of the analysis of road conditions in Saka - Wailulu Village, Taniwel - Saleman Section using the PCI method showed an average PCI value of 72,375 with a verry good rating with 8 types of damage occurring, namely alligator cracking, potholes, block cracking, whaethering or raveling, patching and utility cut patching, joint reflection cracking, shoving and depression.